Validitas dan Reliabilitas The Center for Epidemiologic Studies Depression Scale pada Lansia - ni made ayu wulansari; Ratnasari Ratnasari; Laura Khattrine Noviyanti; Kartini Suhas (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Depression is one of mental health problem which happen to elderly. Elderly with chronic disease will highly risk to have depression. Depression can be measured by CESD-R (The Center for Epidemiologic Studies Depression-Revised). This research was to assess the validity and reliability of it. The respondent who used in this research was 120 persons. The data collection used random sampling and be analyzed used RASCH. The result of reliability is person reliability 0.87, item reliability 0.95 and alpha Cronbach 0.89. the result of validity is raw variance observed 100 % with raw unexplained total 47.5%. 1st contrast 14% and 2nd contrast 7.4%. The study found that CESDR is good instrument to measure depression because it has good reliability and validity.